Pengaruh penggunaan smartphone oleh petani kelapa sawit swadaya dalam meningkatkan literasi media di Desa Pasir Emas Kecamatan Singingi Kabupaten Kuantan Singingi - Patika Riki Darmayanti; Roza Yulida; Arifudin (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This study was aimed to analyze the factors that influence the use of smartphone and analyze the effect of the use of smartphone on increased media literacy by oil palm farmers. The study was conducted on smartphone user oil palm farmers who are members of farmer groups on Pasir Emas Village. This study used a survey method with quantitative descriptive data analysis, which was distributed to 110 respondents with proportional random sampling. The questionnaire was arranged using the Technology Acceptance Model (TAM) theory with a complete construct, while the data processing method used in this study was the Structural Equation Model (SEM). The results showed that the internal characteristics which consisted of age, education level, cosmopolitan and duration of use of smartphones, then external characteristics, namely family support had a significant influence on technology acceptance. These characteristics of farmers were one of the factors that influence the use of smartphones, observed from the duration of farmers using smartphones, the majority of farmers used smartphones 6-7 hours/day. The duration of using smartphone showed user satisfaction and the time spent mingling with technology. The real condition variable of use has a significant influence on the level of media literacy, henceforth, the more often/longer you use the smartphone, the more media literacy of oil palm farmers will be increased. The smartphone features used by farmers to find information were the whatsapp and facebook applications, they share information about oil palm farming.